Dual Tasking : ein neuropsychologisches Testinstrument zur Diskriminierung zwischen Depression und M. Alzheimer - Goerke-Arndt, Franziska; Justus Liebig University Giessen (My University, 2012)
Die Zielsetzung dieser Arbeit war die Untersuchung von in ihren episodischen Gedächtnisleistungen parallelisierten Gruppen von 24 Depressiven und 24 leicht bis mittelschweren AD-Patienten mittels eines neuropsychologischen Testverfahrens, dem Dual Tasking in seiner Papier- und Bleistiftversion, in Hinblick auf dessen Diskriminationsfähigkeit zwischen beiden Gruppen. Im kognitiven Störungsprofil beider Gruppen finden sich Überlappungen vor allen in den episodischen Gedächtnisleistungen, nicht aber bei der geteilten Aufmerksamkeit, welche mit dem Dual Tasking untersucht werden. Den theoretischen Hintergrund hierfür liefert das auf dem Konzept der Zentralen Exekutive (CE, Baddeley, 1986) fußende Dual Task Paradigma, welches Einbußen bei der geteilten Aufmerksamkeit bei AD regelhaft, nicht aber bei nach Alter parallelisierten Gesunden aufzeigte (Della Sala & Logie, 1993). Der Vergleich mit Depressiven und die genauere Untersuchung der einzelnen Komponenten des Dual Taskings stehen noch aus und sind der Inhalt dieser Untersuchung.Um die Diskriminationsfähigkeit des Dual Tasking beurteilen zu können, war, basierend auf dem kognitiven Störungsprofil beider Erkrankungen, die Parallelisierung beider Gruppen nach ihren episodischen Gedächtnisleistungen von zentraler Bedeutung.Die Ergebnisse dieser Untersuchung konnten gemäß den theoretischen Überlegungen hierzu die Fähigkeit des Dual Taskings, zwischen beiden Gruppen zu trennen, klar belegen. Bei der Untersuchung der einzelnen Komponenten des Dual Tasking, die bislang nicht erfolgt ist, erwies sich der für die vorliegende Arbeit neu ermittelte List Memory CORRECT Score als das zwischen Depression und AD am besten diskriminierende Maß in Bezug auf die Trennschärfe, womit sich für weitere Untersuchungen des Dual Tasking neue Möglichkeiten ergeben.Zusammenfassend lässt sich festhalten, dass mit dem Dual Tasking ein viel versprechendes neuropsychologisches Testinstrument vorliegt, besonders, wenn Tests zu episodischen Gedächtnisleistungen nicht zwischen beiden Erkrankungen trennen können. Somit könnte hiermit eine zusätzliche Möglichkeit vorhanden sein, kognitive Defizite bei AD früh zu detektieren und in ihrem Verlauf zu verfolgen.Von theoretischem Interesse kann der Hinweis auf eine spezifische Koordinierungsfunktion für simultan ablaufende Handlungen bei Gesunden sein, die bei AD, nicht aber bei Depression gestört ist.

The purpose of the present study was to compare two groups of 24 depressive patients and 24 patients suffering from mild to moderate Alzheimer´s Disease (AD) by using a neuropsychological test, the Dual Task Paradigm in a paper and pencil version, suitable to discriminate the two groups. The cognitive profile of both diseases shows overlap in several fields, but in particular in episodic memory which is called to be the hallmark of AD but is also described in depression. However, there is no overlap of performance on divided attention tasks, which are not observed in depressives but are well documented in AD, so that tests measuring these performances give promise to be helpful in distinguishing between AD and depression. The theoretical background for this is provided by the Dual Task Paradigm which is based on the concept of a Central Executive (Baddeley, 1986). A specific deficit of this performance was observed in AD but not in healthy aged persons matched for age as first described by Della Sala & Logie (1993). A comparison of Dual Task performance in AD and depressives as well as the analysis of single components represented in this task has not been accomplished so far and therefore the aim of this study is to test the suitability of Dual Tasking for distinguishing between AD and depression. Based on the profile of cognitive deficits characteristic of the two groups, an essential prerequisite for discriminating the groups by their performance on Dual Tasking was to match the participants according to their performance on episodic memory.As expected on the foundings of theory the results of this experiment show that Dual Tasking was capable to discriminate AD-patients from depressive patients even after matching them according to episodic memory. A detailed analysis of the single components of Dual Tasking which had not been done yet - revealed that the subtest List Memory CORRECT Score distinguishes best between the two groups. This score has been newly introduced by us and provides possibilities for further research.In summary, the Dual Task Paradigm appears to be a promising tool for psychopathological assessment in detecting specific cognitive impairments, in particular, if tests measuring impairment of episodic memory are not suitable to discriminate between the two diseases. Thus, an additional possibility has been identified for early detection of cognitive deficits in AD but not in depression. Furthermore, the data could provide theoretical implications for detecting processes in coordinating actions in healthy subjects which are disturbed in AD but not in depression.Additionally, it could also be helpful in monitoring the progression of the disease related to a specific function for tasks damaged only in AD.
Keywords: Dual Tasking; Depression; M. Alzheimer; ddc:610